ANALISIS POLA SPASIAL SUHU PERMUKAAN DI KOTA MATARAM TERKAIT FENOMENA URBAN HEAT ISLAND (UHI) BERDASARKAN FAKTOR EMISIVITAS LAHAN, KERAPATAN VEGETASI DAN JUMLAH KENDARAAN - Wiwit Bayu Adi; Fariz Pribadi Hirsan; Joni Safaat Adiansyah (JURNAL GEOGRAFI, 2021)
The difference in air temperature between the city center and the suburbs is known as the effect of the UHI (Urban Heat Island) phenomenon. In Indonesia, this phenomenon of uneven excess heat is better known as the hot pole of the city. UHI is analogized as an island, which has a surface temperature of hot air that is centered in the area (Urban) and will decrease in temperature in the area (Sub Urban) or the area (Rural) around it. The effect of UHI has become the world's spotlight that must be addressed immediately, because more and more cities are experiencing the effects of this phenomenon, if it continues, it will lead to a higher rate of increase in global warming. Indirectly, Mataram City has experienced the UHI phenomenon which is marked by an increase in air temperature along with an increase in the number of vehicles, a lack of green open space and an increasing number of land conversions into built-up land as housing/settlement areas and city service activities. The purpose of this article is to find out the spatial pattern of surface temperature in Mataram City from 2000 to 2020. The method used is a remote sensing system, by utilizing Landsat 8 Satellite Imagery data. In addition, a simple linear regression analysis method is used to knowing how much influence the independent variable (X) has on the dependent variable (Y). The variables used are the value of vegetation density, number of vehicles and land emissivity as a variable (X) and the value of the spatial pattern of surface temperature as a variable (Y). These three independent variables are what distinguishes this article from previous articles. Therefore, the author tries to redevelop and analyze the UHI phenomenon that is currently happening in the city of Mataram. From the results of the analysis, it was found that the surface temperature value in Mataram City from 2000 to 2020 had a varying temperature trend value, where in 2000 the maximum temperature value reached 28.3oC and in 2020 the trend of the maximum temperature value increased to 35.1oC. Meanwhile, if we look at the distribution of the spatial pattern of surface temperatures in the city of Mataram, it also continues to experience formation and increase, which begins to be concentrated in the middle of the city's activities and begins to spread to the periphery of the city's activity center. The value of the greatest influence resulting from statistical tests shows that the value of vegetation density gives an effect of 56% and is followed by the number of vehicles by 53%, while the smallest influence value is found in the emissivity factor of land with an influence value of 49%.